Expanded host and geographic range of tadpole associations with the Severe Perkinsea Infection group - Smilansky, Vanessa; Jirků, Miloslav; Milner, David S; Ibáñez, Roberto; Gratwicke, Brian; Nicholls, Andrew; Lukeš, Julius; Chambouvet, Aurélie; Richards, Thomas A (Biology letters, 2021)
Severe Perkinsea infection is an emerging disease of amphibians, specifically tadpoles. Disease presentation correlates with liver infections of a subclade of Perkinsea (Alveolata) protists, named Pathogenic Perkinsea Clade (PPC). Tadpole mortality events associated with PPC infections have been reported across North America, from Alaska to Florida. Here, we investigate the geographic and host range of PPC associations in seemingly healthy tadpoles sampled from Panama, a biogeographic provenance critically affected by amphibian decline. To complement this work, we also investigate a mortality event among Hyla arborea tadpoles in captive-bred UK specimens. PPC SSU rDNA was detected in 10 of 81 Panama tadpoles tested, and H. arborea tadpoles from the UK. Phylogenies of the Perkinsea SSU rDNA sequences demonstrate they are highly similar to PPC sequences sampled from mortality events in the USA, and phylogenetic analysis of tadpole mitochondrial SSU rDNA demonstrates, for the first time, PPC associations in diverse hylids. These data provide further understanding of the biogeography and host range of this putative pathogenic group, factors likely to be important for conservation planning.
Keywords: Aljaška; Severní Amerika; Florida; Larva; frog disease; alveolate parasites; larva; Animals; amphibian conservation; zvířata; North America; Phylogeny; fylogeneze; Alaska